2021
DOI: 10.1007/s12015-021-10249-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransductive Differentiation of Hair Follicle Stem Cells Derived from Aged Eyelid Skin into Corneal Endothelial-Like Cells

Abstract: Corneal endothelial insufficiency is one of the leading causes of blindness. The main contemporary treatment for corneal blindness is endothelial keratoplasty, which, however, is unsatisfactory as a medical therapy due to the lack of donor corneas and graft rejection. Therefore, autologous stem cell-based corneal endothelial tissue substitutes may be a promising alternative to conventional grafts in the future. To address the age of most patients suffering from corneal endothelial deficiencies, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…The results demonstrated that the differentiated iCECs on day 24 were mature iCECs. Our data presented here support prior reports that the membrane potential of cells can be measured by the combination of oscilloscope and Transwells to evaluate cell maturity [ 31 ]. Moreover, RNA-seq data identified potential molecular markers of mature iCECs, which may serve as surrogates for predicting their functional properties.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results demonstrated that the differentiated iCECs on day 24 were mature iCECs. Our data presented here support prior reports that the membrane potential of cells can be measured by the combination of oscilloscope and Transwells to evaluate cell maturity [ 31 ]. Moreover, RNA-seq data identified potential molecular markers of mature iCECs, which may serve as surrogates for predicting their functional properties.…”
Section: Discussionsupporting
confidence: 89%
“…Given that TJP1 (ZO-1) , CDH2 (N-cadherin) , ATP1A1 (Na + K + ATPase) and AQP1 play critical roles in the function of CECs, we hypothesize that a prolonged maturation culture might be needed for functional acquisition of iCECs. To demonstrate the functional capacity of iCECs, we performed transendothelial electrical potential difference recording of day 19 and day 24 cells using a Transwell system as described previously [ 31 ]. This transendothelial potential is dependent on continuous tight junctions and the activity of Na + K + ATPase, which is of fundamental importance for the osmotic activity of iCECs.…”
Section: Resultsmentioning
confidence: 99%
“…135 The hair follicular stem cells are multipotent, capable of giving rise to not only the follicle but also the epidermis and the sebaceous gland. 136 Studies showed that hair follicular stem cells could be transdifferentiated into cells that resemble the corneal epithelium and endothelium, 137,138 demonstrating great promise for ocular regeneration.…”
Section: Eyelid Skinmentioning
confidence: 99%
“…Meanwhile, additional candidates for adjunctive therapy are being investigated, such as fibroblast grow factor 1 derivatives which may promote endothelial proliferation and migration [61,62], and other preclinical studies use cells that will not require corneal donation, such as human SC from embryonic [63], induced pluripotent [64–67], umbilical cord-derived [68], dental pulp [69] and eyelid hair follicle-derived [70] sources. None of these approaches are currently in human trials.…”
Section: Endotheliummentioning
confidence: 99%